2011
DOI: 10.2519/jospt.2011.3365
|View full text |Cite
|
Sign up to set email alerts
|

Six Weeks of Balance Training Improves Sensorimotor Function in Individuals With Chronic Ankle Instability

Abstract: T he tendency toward repeated ankle sprains and recurring symptoms (eg, pain, weakness, giving way) has been termed "chronic ankle instability" (CAI) 35 and reported to occur in as high as 40% to 70% of individuals who have sustained a lateral ankle sprain. 7,23,45 Changes in sensorimotor system function are thought to be involved in the decreased postural control and joint position awareness and increased instability found in individuals with CAI. 13,24,46 T T STUDY DESIGN: Prospective cohort study. T T OBJEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 42 publications
3
61
0
3
Order By: Relevance
“…For instance, individuals with CAI improved their dynamic postural control (ie, increased excursion during a Star Excursion Balance Test) after training involving various balance activities in a single-legged stance 11 or balancing on an unstable surface. 10 Therefore, the results of these studies suggested that increased COP excursion while performing dynamic tasks might not necessarily indicate decreased postural stability, as observed in static conditions. This hypothesis needs to be tested, as it could affect the way postural instability is tested in patients with CAI.…”
mentioning
confidence: 92%
“…For instance, individuals with CAI improved their dynamic postural control (ie, increased excursion during a Star Excursion Balance Test) after training involving various balance activities in a single-legged stance 11 or balancing on an unstable surface. 10 Therefore, the results of these studies suggested that increased COP excursion while performing dynamic tasks might not necessarily indicate decreased postural stability, as observed in static conditions. This hypothesis needs to be tested, as it could affect the way postural instability is tested in patients with CAI.…”
mentioning
confidence: 92%
“…31 Rehabilitation programs are typically geared toward improving ankle motion, increasing strength of the lateral stabilizers, and regaining neuromuscular control. 9,45,54 Despite efforts to restore strength and function, many individuals resprain their ankle. 58 Repetitive sprains may increase the risk of ankle osteoarthritis.…”
mentioning
confidence: 99%
“…Two studies used the Foot and Ankle Disability Index to determine self-reported symptoms of CAI. 7,8 The other 2 studies did not include information about the assessment tools used to determine CAI. 4,6 • Three studies demonstrated improvement in static postural stability in single-limb stance after the training protocol.…”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…• Two randomized controlled trials 4,5 and 2 cohort studies 6,7 were included. • The definition of CAI in all 4 studies included a history of more than 1 ankle sprain with residual symptoms, as well as a subjective feeling of the ankle "giving way."…”
Section: Focused Clinical Questionmentioning
confidence: 99%